E- and M-Commerce and Payment Sector Development in Vietnam - International Finance Corporation (International Finance Corporation, Washington, DC, 2017)
This study investigates the state of the electronic (e) and mobile (m)-commerce sector in Vietnam and its impact on the development of cashless payments and online financial services. The e- and m-commerce sector in Vietnam is growing organically. Although still immature and small in volume, advances in the region suggest that the sector will continue to expand and that investment is increasing in startups involved in payments, FinTech, third party logistics, and software aiming to support development. Vietnam has one of the fastest growing economies globally and the World Bank estimates that its GDP per capital will double in the next decade. It is one of the most populous countries in South East Asia with a majority of its inhabitants under 30. The rest of this document is structured as follows: Section two provides a short overview of the research conducted with end users and clients of e- and m-commerce firms; Section three describes the company survey methodology and the survey population of e-and m-commerce and support service firms; Section four presents the results from the survey including findings about payment acceptance and usage by e-and m-commerce firms and their clients as well as the business of payments and related services and logistics providers supporting the industry in Vietnam; and Section five provides key conclusions. The Annex to this report contains information about the surveyed companies, questionnaires and a snap shot of the front running firms and investors that are active in this market segment.